2022
DOI: 10.1155/2022/5425478
|View full text |Cite
|
Sign up to set email alerts
|

Oral Squamous Cell Carcinoma: The Role of BIRC6 Serum Level

Abstract: Background. Different factors are involved in the incidence, etiology, metastasis, diagnosis, and treatment of oral squamous cell carcinoma, including apoptosis inhibitor proteins. Baculoviral IAP repeat containing protein 6 (BIRC6) is one of the apoptosis inhibitor proteins contributing to cancer cells’ survival in many cancer types with diagnostic and treatment importance. This study is aimed at assessing the serum level of BIRC6 in oral squamous cell carcinoma. Materials and Methods. In this retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Our study found that BIRC6 was overexpressed in OSCC cases, and to the best of our knowledge, this is the first report to clarify BIRC6 expression in OSCC. However, Banakar et al assessed the serum level of BIRC6 in OSCC and found no significant difference in the serum levels of BIRC6 between patients with OSCC and healthy individuals [35]. Other studies have also investigated antiapoptotic markers in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that BIRC6 was overexpressed in OSCC cases, and to the best of our knowledge, this is the first report to clarify BIRC6 expression in OSCC. However, Banakar et al assessed the serum level of BIRC6 in OSCC and found no significant difference in the serum levels of BIRC6 between patients with OSCC and healthy individuals [35]. Other studies have also investigated antiapoptotic markers in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…We also suggested that upregulation of CD274 inhibited proliferation and invasion of A549 cells and increased apoptosis in lung cancer cells. The CD274 gene encodes PD-L1, a major co-inhibitory checkpoint signal that controls T-cell activity ( 53 , 54 ). A study showed a significant increase in PD-L1 in shGBE1 A549 cells and a negative correlation between PD-L1 and GBE1 ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…However due to the great genetic and epigenetic heterogeneity of this tumor, identifying a sensitive and specific biomarker has remained a challenge. 2 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%